Sistem Pendukung Keputusan Penilaian Kinerja Pegawai Kontrak Di Kantor Dinas Pendidikan Kabupaten Labuhanbatu Menggunakan Metode ARAS (Additive Ratio Assessment) - Rita Sari Siregar (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
Human resources are a very important component as the driving force of an agency. The quality of human resources in an agency is very influential on the performance of an agency, so it is necessary to evaluate the performance of contract employees at the Labuhanbatu District Education Office to improve the performance of the agency. So far, the performance appraisal of contract employees at the Office of Education has not been based on calculating the value of definite evaluation criteria, so it is considered not objective. This study aims to implement the Additive Ratio Assessment (ARAS) method, which is a method used for ranking criteria. In the decision support system for assessing the performance of contract employees at the Labuhanbatu District Education Office so that assessments can be faster and objective. The ARAS method was chosen because it is considered capable of solving multi-criteria problems. From the results of testing this system, it can be seen that this system can run well when carrying out the process of evaluating employee performance according to the weight of predetermined criteria.